Comprehensive Review of Machine Learning (ML) in Image Defogging: Taxonomy of Concepts, Scenes, Feature Extraction, and Classification techniques - Arif Z.H.; Mahmoud M.A.; Abdulkareem K.H.; Mohammed M.A.; Al-Mhiqani M.N.; Mutlag A.A.; Damaevi?ius R. (John Wiley and Sons Inc, 2023)
Extraction; Feature extraction; Image denoising; Image segmentation; Classification technique; Feature extraction and classification; Feature extraction techniques; Features extraction; Images processing; Machine learning algorithms; Machine learning methods; Research areas; Sensory system; Visual sensory; Image classification